River Ecological Restoration and Groundwater Artificial Recharge - Zhai, Yuanzheng; Wu, Jin; Wang, Huaqing (MDPI - Multidisciplinary Digital Publishing Institute, 2022)
Three of the eleven papers focused on groundwater recharge and its impacts on the groundwater regime, in which recharge was caused by riverbed leakage from river ecological restoration (artificial water replenishment). The issues of the hydrogeological parameters involved (such as the influence radius) were also reconsidered. Six papers focused on the impact of river ecological replenishment and other human activities on river and watershed ecology, and on groundwater quality and use function. The issues of ecological security at the watershed scale and deterioration of groundwater quality were of particular concern. Two papers focused on water resources carrying capacity and water resources reallocation at the regional scale, in the context of the fact that ecological water demand has been a significant topic of concern. The use of unconventional water resources such as brackish water has been emphasized in the research in this issue.